Sensing and data fusion to characterize vehicle behavior surrounding autonomous vehicles - Ang, Chon Chia, author; Bradley, Thomas, advisor; Bechara, Samuel, committee member; Kamran, Eftekhari Shahroudi, committee member (Colorado State University. Libraries, 2022)
Under the request and funding of Colorado Department of Transportation (CDOT), the Colorado State University (CSU) Autonomous Vehicle Research Labs aims to develop a portable and flexible tracking array as a means to collect data pertaining to travel trajectories of vehicles approaching an autonomous vehicle with and without autonomous status indication. This paper will outline the logic, structure and process of designing various features of an autonomous tracking array along with any modifications made as result of feedback from multiple users. In addition, this paper will cover how the tracking array was used to collect left-lane travel trajectories of Human Driven Vehicle (HDV) in residential lanes with and without the presence of an obstructing vehicle as well as highlighting any significant difference in Fuel Economy (FE) distribution in both scenarios. The purpose of such experiment is to address whether the presence of an obstruction results in a significant decrease in FE of HDV. Findings of the experiment indicates the presence of obstruction in residential lanes results in results in a lower value FE distribution for HDV. Finally, this paper will cover challenges faced in designing the tracking array, collecting data in residential lanes along with any additional work done by the author during his time at CSU.